The Improving Fine Motor Skills Through Patterned Paper in Group A of PAUD Bunda Pertiwi - Sri Ayuni Lestari; M Arif Syarif H; Andi Ali Kisai (EDUKASI, 2026)
This research was motivated by the low fine motor skills of 4-5-year-old children in Group A of Bunda Pertiwi Early Childhood Education (PAUD) in Tengah Tani District, Cirebon Regency, particularly in cutting activities. Based on initial observations, approximately 70% of the 13 children still experienced difficulty coordinating eye-hand movements. This study aimed to improve children's fine motor skills through the use of pattern paper. The method used was Classroom Action Research (CAR) modeled after Kemmis and McTaggart, conducted in two cycles. Data collection techniques included observation, interviews, and documentation, with descriptive quantitative and qualitative data analysis. The results showed an increase in children's fine motor skills, from 30% in the pre-cycle to 55% in the first cycle, and reaching 85% in the second cycle. Improvements were seen in children's ability to cut according to patterns, eye-hand coordination, and neatness of cutouts. Thus, pattern paper media is effective in improving fine motor skills in early childhood.